2020
DOI: 10.7150/jca.39854
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptomic study of circRNAs expression profile in sorafenib resistant hepatocellular carcinoma cells

Abstract: The anti-angiogenic drugs represented by sorafenib over the years have always been the first-line treatment of hepatocellular carcinoma (HCC), but the drug resistance has always been a "bottleneck" in curative effect. Recently, aberrant expression of circular RNA (circRNA) is considered to play a crucial role in many types of cancers. However, the genome-wide expression pattern of circRNAs in sorafenib-resistant HCC cells remains unknown. Herein, we identified 1717 differentially expressed circRNAs with 559 up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
(27 reference statements)
1
12
0
Order By: Relevance
“…4 d, e) were chosen for further validation. Among these circRNA candidates, approximately half of them were upregulated in sorafenib-resistant Huh7 cells according to the previously published RNA-seq data [ 25 ] (Additional file 1 : Figure S8d). The circular structure of these circRNA candidates was confirmed by RNase R treatment (Additional file 1 : Figure S8e).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…4 d, e) were chosen for further validation. Among these circRNA candidates, approximately half of them were upregulated in sorafenib-resistant Huh7 cells according to the previously published RNA-seq data [ 25 ] (Additional file 1 : Figure S8d). The circular structure of these circRNA candidates was confirmed by RNase R treatment (Additional file 1 : Figure S8e).…”
Section: Resultsmentioning
confidence: 92%
“…However, resistance to sorafenib frequently occurs and limits the benefit of such therapeutic option. Recently, genome-wide expression pattern of circRNAs in sorafenib-resistant HCC cells has been analyzed, and over 1000 differentially expressed circRNAs have been identified [ 25 ], indicating a potential role of circRNAs in the development of sorafenib resistance. To test this hypothesis, we performed drug selection screening with the larger Cas13d library to identify circRNAs, whose inhibition could increase the therapeutic efficacy of sorafenib in Huh7 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 4 Some circRNAs have been recently identified as important regulators in HCC chemoresistance by functioning as sponges of microRNAs (miRNAs). 5 Li et al showed that circRNA F-box protein 11 (circFBXO11) enhanced oxaliplatin resistance of HCC by sequestering miR-605. 6 Luo et al demonstrated that circ_101505 regulated HCC cell resistance to cisplatin (DDP) by working as a miR-103 sponge.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, some of these circRNAs had been demonstrated to be related to cancer progression. For example, hsa_circ_0084663 was validated to be related to sorafenib-resistant liver cancer [ 42 ]. Very interestingly, we found that hsa_circ_0061776 and hsa_circ_0006528 were also upregulated in colon samples by analyzing the supplementary table in an independent report [ 25 ].…”
Section: Resultsmentioning
confidence: 99%